The Tuberous Sclerosis 2000 Study: presentation, initial assessments and implications for diagnosis and management. Issue 11 (3rd August 2011) - Yates, John RW; MacLean, Cathy; Higgins, J Nicholas P; Humphrey, Ayla; le Maréchal, Kate; Clifford, Michelle; Carcani-Rathwell, Iris; Sampson, Julian R; Bolton, Patrick F
Abstract : Aims: The Tuberous Sclerosis 2000 Study is the first comprehensive longitudinal study of tuberous sclerosis (TS) and aims to identify factors that determine prognosis. Mode of presentation and findings at initial assessments are reported here. Methods: Children aged 0–16 years newly diagnosed with TS in the UK were evaluated. Results: 125 children with TS were studied. 114 (91%) met clinical criteria for a definite diagnosis and the remaining 11 (9%) had pathogenic TSC1 or TSC2 mutations. In families with a definite clinical diagnosis, the detection rate for pathogenic mutations was 89%. 21 cases (17%) were identified prenatally, usually with abnormalities found at routine antenatal ultrasound examination. 30 cases (24%) presented before developing seizures and in 10 of these without a definite diagnosis at onset of seizures, genetic testing could have confirmed TS. 77 cases (62%) presented with seizures. Median age at recruitment assessment was 2.7 years (range: 4 weeks–18 years). Dermatological features of TS were present in 81%. The detection rate of TS abnormalities was 20/107 (19%) for renal ultrasound including three cases with polycystic kidney disease, 51/88 (58%) for echocardiography, 29/35 (83%) for cranial CT and 95/104 (91%) for cranial MRI. 91% of cases had epilepsy and 65% had intellectual disability (IQ<70). Conclusions: Genetic testing can be valuable in confirming the diagnosis. Increasing numbers of cases present prenatally or in early infancy, before onset of seizures, raising important questions about whether these children should have EEG monitoring and concerning the criteria for starting anticonvulsant therapy.